2014
DOI: 10.1080/15583058.2014.951792
|View full text |Cite
|
Sign up to set email alerts
|

Structural Identification of a Masonry Tower Based on Operational Modal Analysis

Abstract: The structural assessment of a Cultural Heritage building is a step-by-step process that merges research methodologies and information from several disciplines. Although general rules that can be applied to all historic constructions are very difficult to define, it is generally agreed (Binda, Saisi, and Tiraboschi 2000) that the first phase of a correct diagnostic approach (i.e., the evaluation of the current health state or performance of the building) consists of the following tasks:• Historic and documenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
65
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 16 publications
3
65
1
Order By: Relevance
“…In particular, while the use of Operational Modal Analysis (OMA) techniques is well-established for performing dynamic structural investigations and/or implementing continuous monitoring of relatively new slender structures [8,9], their application in the context of heritage monumental buildings is far less common. A few documented applications of vibration-based monitoring to monumental buildings are however available, whereby some literature studies have proposed the use of OMA techniques for the dynamic identification of masonry civil and bell towers [10,11,12]. On the contrary, applications to different kinds of historic structures are quite rare and only a few studies have proposed to use OMA techniques in the context of continuous dynamic monitoring systems [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, while the use of Operational Modal Analysis (OMA) techniques is well-established for performing dynamic structural investigations and/or implementing continuous monitoring of relatively new slender structures [8,9], their application in the context of heritage monumental buildings is far less common. A few documented applications of vibration-based monitoring to monumental buildings are however available, whereby some literature studies have proposed the use of OMA techniques for the dynamic identification of masonry civil and bell towers [10,11,12]. On the contrary, applications to different kinds of historic structures are quite rare and only a few studies have proposed to use OMA techniques in the context of continuous dynamic monitoring systems [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the updated models can be used to predict future structural behavior or diagnose potential damage, when dynamics alterations are detected on buildings [14]. One example of these kinds of study is reported by Gentile et al [15]. They performed an extensive structural assessment program on a historic bell tower.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies investigated to determine the modal parameters of historical masonry structures [5][6][7][8][9]. Because only few studies [10][11] were conducted about the determining the modal parameters of historical masonry minarets, in this study, it is intended to perform experimentally and numerically analyses to investigate the modal parameters of a masonry type historical minaret.…”
Section: Introductionmentioning
confidence: 99%